Concerns regarding sepsis identification using ICD codes in MIMIC-IV based research - Guangdong Wang; Yaxin Zhang (Journal of Translational Medicine)
Abstract In the article “Comparison of rhythm and rate control medications for new-onset atrial fibrillation in septic patients: MIMIC-IV database analysis”, Weng et al. used ICD-9/ICD-10 codes to define sepsis. However, we suggest that using the Sepsis-3.0 criteria, which incorporates SOFA scoring and infection evidence, would provide a more accurate diagnosis. The MIMIC-IV database offers a derived table based on Sepsis-3.0, which could improve cohort definition and enhance the study’s clinical relevance. We recommend that future research adopt Sepsis-3.0 or perform sensitivity analyses to improve result robustness.